An unusual case of SMMCI syndrome: supernumerary midline central incisor in siblings. (1st January 2020) - Morison, Hannah; Gillgrass, Toby; Dunbar, Evelyn; Welbury, Richard
Abstract : This is the first reported case of siblings with Solitary Median Maxillary Central Incisor (SMMCI) syndrome presenting with an erupted single symmetrical central maxillary midline incisor between normal central incisors. Usually only one central incisor is present. This case is also interesting as the tooth described could have been mistaken for a mesiodens, however, a mesiodens is not symmetrical and usually erupts between the maxillary central incisors and sits slightly to the right or left of the midline. CPD/Clinical Relevance: This case highlights the fact that SMMCI should not be considered as a simple dental anomaly because it may be associated with more complex craniofacial malformations.